Soon by you - Adler, Dahlia (St. Martin's Griffin, 2026)
""Fun, fan-yourself sexy, and full of heart." - Rosie Danan, USA Today bestselling author of The Intimacy Experiment 27 Dresses meets The Intimacy Experiment in this sexy, emotional, opposites-attract rom-com set in New York City's Modern Orthodox community. Arielle Becker is one hora away from a meltdown. After one too many bridesmaid gigs-complete with Spanx, heels, and hideous dresses-she's officially over love and its overpriced trappings. Especially when they keep coming with the same smug, judgmental wedding singer. Judah Klein is New York's go-to Modern Orthodox wedding singer and most eligible bachelor. Years of failed setups have left him jaded, until repeated clashes with a fiery bridesmaid wake him right up. But when snarks turn to sparks, and fights turn to feelings, things get complicated. Arielle is not a girl who settles down. And Judah is not a guy who hooks up. So why does walking away feel impossible? "I came for the sexy opposites-attract romance, stayed for the joyous celebration of Jewish life and community, and fell hard for Judah, Ari, and their journey toward one another but also toward finding themselves. Soon by You somehow manages to be both sizzlingly hot and meltingly sweet at the same time; the only thing I disliked about the book was that it had to end. I can't wait for more hot Jewish romance from Dahlia Adler!" - Amanda Elliot, USA Today bestselling author of Love You a Latke "Dahlia Adler's Soon by You is a romance that sets itself apart. Readers are afforded a rare glimpse inside the Orthodox Jewish dating scene in a way that's both immersive and authentic. But it's the off-the-charts chemistry between the hero and heroine that makes this story truly shine. A little Pride and Prejudice, a little Fifty Shades of Grey, and a whole lot of Chutzpah!" - Heidi Shertok, author of Unorthodox Love"-- Provided by publisher.